ECONOMICAL BEHAVIOR ANALYSIS OF AGRICULTURAL COMPANIES IN IRAQ USING TRANSLOG COST FUNCTION - & Ali, AJ-Jiboory (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research aims to identify the productive relationship nature among the elements used in the agricultural companies by estimating the translog cost function. It also aims to recognize the possibility of substituting these elements with each other, to identify the nature of revenues, and economies scale through elasticity of other cost. This research goes further to define the typical use of resources, identify the performance of the companies and their contribution in controlling their cost, and estimating elasticity of substitution (Allen-Uzawa), (Morishima).  The translog cost function was estimated so as the total cost of the agricultural companies is a function of the prices of production and production quantity output  elements. The shares of production elements  (labor, capital, commodity and services requisites)  were derived from this translog  cost function by using SUR method and Eviews9 after applying  symmetry and homogeneity.  It was clear, in the translog cost function or in the production elements share functions,  that there is a strong correlation between the prices of the production elements and the total costs.  If prices increase, their contribution share in the total costs increases. Calculation were made among production elements, the self demand, cross, and substitution elasticity. Results show that the self demand was  ( 0.64،2.01 ، 0.02،2.28). This result clarifies the share of the production elements (labor, capital, commodity and services requisites)  in the total costs of the agricultural companies. The results show that increasing in the wage of labor, capital prices, and commodity and services requisites with 1% had led to increase in the demand on labor, capital prices, and commodity and services requisites   with ( 0.64%, 2.10%, 0.02%, and 2.28% ) respectively. The elasticity (Allen – Uzawa) of partial substitution between the labor and capital was 0.0009. This indicates that increasing the capital price value to the labor wage with rate of 1% will decrease the capital element rate to the labor wage with 0.0009%. This is a very low rate. The elasticity of partial substitution (Morishima) for the elements of production shares was (2.1, 0.02, 2.27, and 0.06).